2010
DOI: 10.1007/s10689-009-9316-y
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after prophylactic total gastrectomy

Abstract: Hereditary diffuse gastric cancer is an autosomal dominant inherited cancer predisposition syndrome characterized by susceptibility to diffuse gastric and lobular breast cancers. Since current screening options for diffuse gastric cancer are ineffective, prophylactic total gastrectomy (PTG) is a recommended option for unaffected germline CDH1 mutation carriers. It is unknown whether pregnancy after surgery is possible or advisable due to potential maternal nutritional deficiencies. In this report we describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Some experts say that delay of prophylactic gastrectomy in young female CDH1 mutation carriers is reasonable, considering the metabolic consequences of total gastrectomy during pregnancy [5]. A recent study, however, has demonstrated that a successful term pregnancy following prophylactic gastrectomy is possible [77].…”
Section: Discussionmentioning
confidence: 99%
“…Some experts say that delay of prophylactic gastrectomy in young female CDH1 mutation carriers is reasonable, considering the metabolic consequences of total gastrectomy during pregnancy [5]. A recent study, however, has demonstrated that a successful term pregnancy following prophylactic gastrectomy is possible [77].…”
Section: Discussionmentioning
confidence: 99%
“…Although scientific data are lacking concerning timing of prophylactic gastrectomy and family planning, it is entirely possible for women to give birth to a healthy child after gastrectomy. 52 Nutritional advice and follow-up with a dietician within this context is essential.…”
Section: Genetic Counselling and Mutation Analysismentioning
confidence: 99%
“…Although Kaurah et al showed no adverse outcomes of seven pregnancies in four women (of whom three CDH1 mutation carriers) after gastrectomy and several studies showed no increase of poor pregnancy outcomes after gastrectomies for reasons other than cancer, a critical attitude toward the sequence of pregnancies and prophylactic surgery is recommended. [42][43][44] In our opinion, there is no reason for informing future parents about the risk of CL/P in offspring as integral part of genetic counseling in all HDGC families. However, taking a family history in HDGC families should include the occurrence of CL/P in relatives.…”
Section: Implications For Clinical Practice and Genetic Counselingmentioning
confidence: 99%